Digital marketing excellence : planning, optimizing and integrating online marketing - Chaffey, Dave, 1963-; Smith, P. R. 1957- (Routledge, Taylor & Francis Group, 2023)
"Now in its sixth edition, the hugely popular Digital Marketing Excellence is a practical guide to creating and executing integrated digital marketing plans, combining established approaches to marketing planning with the creative use of new digital models and digital tools. Written by two highly experienced digital marketing consultants, the book shows you how to: Draw up an outline integrated digital marketing plan Evaluate and apply digital marketing principles and models Integrate online and offline communications Implement customer-driven digital marketing as part of digital transformation Reduce costly trial and error Measure and enhance your digital marketing Learn best practices for reaching and engaging your audiences using the key digital marketing platforms. This new edition has been streamlined to seamlessly integrate the latest developments in digital analytics, ethics and privacy, Predictive Analytics, Machine Learning and Artificial Intelligence. Including new international case studies and up-to-date examples throughout, this book cuts through the jargon to show marketers how to leverage data and digital technologies to their advantage. Offering a highly structured and accessible guide to a critical and far-reaching subject, Digital Marketing Excellence, 6th edition, provides a vital reference point for all digital marketing students, and managers involved in digital marketing strategy and implementation. Online resources have been fully updated for the new edition and include a new set of PowerPoint slides and a full test bank of questions and exercises"- Resumé vydavatel